Contemporary Approach to Heavily Calcified Coronary Lesions - Carlotta Sorini Dini; Giulia Nardi; Francesca Ristalli; Alessio Mattesini; Brunilda Hamiti; Carlo Di Mario (Interventional Cardiology: Reviews, Research, Resources)
Percutaneous treatment of heavily calcified coronary lesions still represents a challenge for interventional cardiology, with higher risk of immediate complications, late failure due to stent underexpansion and malapposition, and consequently poor clinical outcome. Good characterisation of calcium distribution with multimodal imaging is important to improve the successful treatment of these lesions. The use of traditional or new dedicated devices for the treatment of calcified lesions allows better lesion preparation; therefore, it is important that we know the different mechanisms and technical features of these devices.